The Prediction Model of Human Household Behavior of the Refuse Management System with Artificial Neural Network - Rohana Sham; Nor Aziyatul Izni; Nor Asiah Mahmood; Nur Ilyana Ismarau Tajuddin (Malaysian Association of Consumer and Family Economics (MACFEA), 2024)
Indexed by Scopus/MyCite